Comparative Study of NAP-XPS and Cryo-XPS for the Investigation of Surface Chemistry of the Bacterial Cell-Envelope - Kjærvik, Marit; Ramstedt, Madeleine; Schwibbert, Karin; Dietrich, Paul M.; Unger, Wolfgang E. S. (Frontiers in Chemistry, 2021)
Bacteria generally interact with the environment via processes involving their cell-envelope. Thus, techniques that may shed light on their surface chemistry are attractive tools for providing an understanding of bacterial interactions. One of these tools is Al Kalpha-excited photoelectron spectroscopy (XPS) with an estimated information depth of <10 nm. XPS-analyses of bacteria have been performed for several decades on freeze-dried specimens in order to be compatible with the vacuum in the analysis chamber of the spectrometer. A limitation of these studies has been that the freeze-drying method may collapse cell structure as well as introduce surface contaminants. However, recent developments in XPS allow for analysis of biological samples at near ambient pressure (NAP-XPS) or as frozen hydrated specimens (cryo-XPS) in vacuum. In this work, we have analyzed bacterial samples from a reference strain of the Gram-negative bacterium Pseudomonas fluorescens using both techniques. We compare the results obtained and, in general, observe good agreement between the two techniques. Furthermore, we discuss advantages and disadvantages with the two analysis approaches and the output data they provide. XPS reference data from the bacterial strain are provided, and we propose that planktonic cells of this strain (DSM 50090) are used as a reference material for surface chemical analysis of bacterial systems.